Combined Laser-Doppler Flowmetry and Spectrophotometry: Feasibility Study of a Novel Device for Monitoring Local Cortical Microcirculation during Aneurysm Surgery - Sommer, Björn; Kreuzer, Maximilian; Bischoff, Barbara; Wolf, Dennis; Schmitt, Hubert; Eyupoglu, Ilker Y.; Rössler, Karl; Buchfelder, Michael; Ganslandt, Oliver; Wiendieck, Kurt (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Monitoring of cortical cerebral perfusion is essential, especially in neurovascular surgery.Study Aims To test a novel noninvasive laser-Doppler flowmetry and spectrophotometry device for feasibility during elective cerebral aneurysm surgery.Material and Methods In this prospective single-institution nonrandomized trial, we studied local cerebral microcirculation using the noninvasive laser-Doppler spectrophotometer “Oxygen-to-see” (O2C) in 20 consecutive patients (15 female, 5 male; median age: 60.5 ± 11.7 years) who were operated on for incidental cerebral aneurysms. Capillary-venous oxygenation (oxygen saturation [“SO2”]), postcapillary venous filling pressures (relative hemoglobin content [“rHb”]), blood cell velocity (“velo”), and blood flow (“flow”) were measured in 7-mm tissue depth using a subdural fiberoptic probe.Results Representative recordings were acquired immediately after dural opening over a median time span of 88 ± 21.8 seconds (range: 60–128 seconds) before surgical manipulation. Baseline values (median ± 2 standard deviations) of brain perfusion as measured with the O2C device were SO2, 39 ± 16.6%; rHb, 53 ± 18.6 arbitrary units (AU); velo, 60 ± 20.4 AU; and flow, 311 ± 72.8 AU. Placement of the self-retaining retractor led to a decrease in SO2 of 17% ± 29% (p < .05) and flow of 10% ± 11% (p < .01); rHb increased by 18% ± 20% (p < .01), and velo remained unchanged. Retractor removal caused the opposite with an increased flow of 10% ± 7% (p < 0.001) and velo (3% ± 6%, p = 0.11), but a decrease in SO2 of 24% ± 33% (p = 0.09) and rHb of 12% ± 20% (p =0.18). No neurologic or surgical complications occurred.Conclusion Using this novel noninvasive system, we were able to measure local cerebral microcirculation during aneurysm surgery. Our data indicate that this device is able to detect changes during routine neurosurgical maneuvers. Thus it may be useful for early detection of cerebral microcirculatory disturbances.
Keywords: cerebral blood flow; cerebral oxygen saturation; intraoperative neuromonitoring; noninvasive diagnostics